Comparison of GFR calculation methods: MDRD and CKD-EPI vs. 99mTc-DTPA tracer clearance rates. (June 2013) - Dias, André H.; Pintão, Sophia; Almeida, Pedro; Martins, Teresa
Abstract Introduction. Glomerular filtration rate (GFR) is considered the best index of kidney function. The Modification of Diet in Renal Disease (MDRD)-Study equation has gained worldwide acceptance for estimating GFR from serum creatinine. Recently the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) group developed a new equation that claims to be more accurate and could replace MDRD for routine clinical use. Nuclear medicine methods are accepted as more accurate, and have become regular practice provided they are easily available. The aim of this study was to evaluate how indirect GFR calculations correlated with the nuclear medicine method. Materials and methods. The authors compared 99mTc-DTPA clearance using the Gates method and a two-blood sample method with MDRD and CKD-EPI, in a population of renal donor candidates and oncological patients treated with nephrotoxic chemotherapy. Results. Our results showed that even though both equations provided a good correlation (p < 0.001) with GFR evaluated by the nuclear medicine method, they underestimated the GFR value in comparison to nuclear medicine methods. Our study also found that CKD-EPI was superior to MDRD. Conclusion. Using purely creatinine-based GFR estimates can lead to complications in clinical practice, especially when correct GFR values are mandatory, like when calculating adequate chemotherapy dosage, and should be used with caution. When the more accurate nuclear medicine methods are unavailable due to cost or accessibility issues, our study showed that the new CKD-EPI appears to reflect GFR results more accurately than MDRD, and thus should be the method of choice for estimating GFR.